Efficient bacterial capture with amino acid modified magnetic nanoparticles - Jin, Yinjia; Liu, Fei; Chao Shan; Meiping Tong; Yanglong Hou (Water Research, 2014)
Traditional chemical disinfectants are becoming increasingly defective due to the generation of carcinogenic disinfection byproducts and the emergence of antibiotic-resistant bacterial strains. Functionalized magnetic nanoparticles yet have shown great application potentials in water treatment processes especially for bacterial removal. In this study, three types of amino acids (arginine, lysine, and poly-l-lysine) functionalized Fe3O4 nanoparticles (Fe3O4@Arg, Fe3O4@Lys, and Fe3O4@PLL) were prepared through a facile and inexpensive two-step process. The amino acid modified Fe3O4 nanoparticles (Fe3O4@AA) showed rapid and efficient capture and removal properties for both Gram-positive Bacillus subtilis (B. subtilis) and Gram-negative Escherichia coli 15597 (E. coli). For both strains, more than 97% of bacteria (initial concentration of 1.5 × 107 CFU mL−1) could be captured by all three types of magnetic nanoparticles within 20 min. With E. coli as a model strain, Fe3O4@AA could remove more than 94% of cells from solutions over a broad pH range (from 4 to 10). Solution ionic strength did not affect cell capture efficiency. The co-presence of sulfate and nitrate in solutions did not affect the capture efficiency, whereas, the presence of phosphate and silicate slightly decreased the removal rate. However, around 90% and 80% of cells could be captured by Fe3O4@AA even at 10 mM of silicate and phosphate, respectively. Bacterial capture efficiencies were over 90% and 82% even in the present of 10 mg L−1 of humic acid and alginate, respectively. Moreover, Fe3O4@AA nanoparticles exhibited good reusability, and greater than 90% of E. coli cells could be captured even in the fifth regeneration cycle. The results showed Fe3O4@AA fabricated in this study have great application potential for bacteria removal from water.
Keywords: Amino acid; Bacteria capture; Competitive anions; Magnetic nanoparticles; Natural organic matter; Reuse